(NsIMMETRIQ GLAZAMI HIMIKA (B:s (NpER(B. (NS ANGL(B. /s - (NhARGITTAI(B, (Ni[TWANs; (NhARGITTAI(B, (NmAGDOLXNAs; (NmASTR@KOW(B, (Nw(B.(Ns(B.s ((NmOSKWA (B:s (NmIR(B,s, 1989)
(NbIBLIOGR(B. (NW KONCE GLAWs
(NpREDM(B. (NUKAZ(B.: (NS(B. 484-491s
Keywords: (NsIMMETRIQ W HIMIIs